Pehuen-có: Al rescate de un tesoro bonaerense - Celsi, Cintia; Monserrat, Ana Laura; Lejarraga, Reginaldo; Doiny Cabré, Cristóbal (Revista Aves Argentinas, 2006)
Accedé al artículo ingresando a la revista (hacé click sobre la portada y/o el número).